Derivation of Some Basic Laws of Rarefied Gas Dynamics for Quantum Gases and Low-Dimensional Systems. Issue 2 (23rd February 2017) - Babac Schubler, Gulru
ABSTRACT: Boltzmann Equation is linearized for quantum gases under the consideration of the dimensional dependencies. The derivation of this new form is presented and discussed for the basic phenomena in rarefied gas dynamics. The effects of quantum contribution and dimensional dependency are analyzed. It is shown that, the introduced form have to be used to analyze transport properties in low-dimensional systems and for the systems which the quantum character arises in.